2009
DOI: 10.1084/jem.20090093
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking T cell immunity in oropharyngeal candidiasis

Abstract: The disproportionate increase in oropharyngeal candidiasis (OPC) compared with systemic and vaginal candidiasis in female patients with AIDS has been a paradox for almost three decades. New data now show that severe OPC develops in Th17-deficient mice, but not Th1-deficient mice, implicating Th17-induced effector molecules in resistance to oral disease. These findings clarify and extend our current thinking about how CD4 T cell deficiency influences susceptibility to OPC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 37 publications
1
32
0
4
Order By: Relevance
“…Murine and rat models have been valuable in advancing our understanding of Candida pathogenicity, antifungal pharmacokinetics, and the immune responses to Candida, including Candida vaginitis (reviewed in references 43, 88, and 177). Infection with C. albicans in these rodents is a de novo event in a naïve host which differs significantly from humans, who develop immune responses to Candida early in life, as C. albicans is a commensal organism of the gastrointestinal tract and often of the genital tract (43,88,198).…”
Section: Animal and Other Models For Genitourinary Candidiasismentioning
confidence: 99%
“…Murine and rat models have been valuable in advancing our understanding of Candida pathogenicity, antifungal pharmacokinetics, and the immune responses to Candida, including Candida vaginitis (reviewed in references 43, 88, and 177). Infection with C. albicans in these rodents is a de novo event in a naïve host which differs significantly from humans, who develop immune responses to Candida early in life, as C. albicans is a commensal organism of the gastrointestinal tract and often of the genital tract (43,88,198).…”
Section: Animal and Other Models For Genitourinary Candidiasismentioning
confidence: 99%
“…However, disruptions in host immune status, barrier function, or local microenvironment (including microbiota composition) can lead to changes in C. albicans growth and physiology (gene/protein expression, metabolism, morphology), which can cause host damage, both microbe mediated and/or host mediated. Depending on the magnitude of damage, disease ensues, which can be acute and/or recurrent in nature (4,(17)(18)(19). As a result, C. albicans infections are recognized as a serious public health challenge with high clinical and socioeconomic importance, representing one of the most prevalent agents identified in nosocomial infections (10,20,21).…”
Section: Candida Albicans: a Versatile Fungal Pathogenmentioning
confidence: 99%
“…Originally, it was thought that the primary protective mechanism by CD4 ϩ T cells was the Th1 phagocyte-dependent response (37). However, the discovery of the Th17 axis and subsequent in vivo studies using the OPC model identified the CD4 ϩ Th17 response as the primary protective response (17,50). Importantly, in the absence of interleukin-17 (IL-17) and related cytokines IL-12 and gamma interferon (IFN-␥), innate cell recruitment, activation, and phagocytosis of C. albicans cells fail to occur.…”
Section: Fitting C Albicans Within the Damage Response Frameworkmentioning
confidence: 99%
“…Despite its prevalence, the pathogenesis of DS and the role of the immune response are not understood. The current dogma for the other major form of oral candidiasis, oropharyngeal candidiasis (OPC), is that a deficiency or reduction in Th1 or Th17 responses is associated with susceptibility to infection (16,26,37). As such, OPC predominately affects individuals with T cell deficiencies such as AIDS patients, infants, and patients receiving immunosuppressive therapy.…”
Section: Enture Stomatitis (Ds) Is An Inflammatory Fungal Infectionmentioning
confidence: 99%